Helicobacter infection alters MyD88 and Trif signaling in response to intestinal ischemia/reperfusion - Hoffman, Sara M.; Wang, Hua; Pope, Michael R.; Fleming, Sherry D. (My University, 2013)
Ischemia/reperfusion-induced intestinal injury requires both toll-like receptor 4 (TLR4) signaling through myeloid differentiation primary response gene (88) (MyD88) and complement activation. As a common Gram negative intestinal pathogen, Helicobacter hepaticus signals through TLR4 and up-regulates the complement inhibitor, decay accelerating factor (DAF; CD55). Since ischemia/reperfusion (IR) is complement dependent, we hypothesized that Helicobacter infection may alter IR-induced intestinal damage. Infection increased DAF transcription and subsequently decreased complement activation in response to IR without altering intestinal damage in wildtype mice. IR induced similar levels of DAF mRNA expression in uninfected wildtype, MyD88-/- or Trif deficient mice. However, during infection, IR-induced DAF transcription was significantly attenuated in Trif deficient mice. Similarly, IR-induced intestinal damage, complement component 3 (C3) deposition and prostaglandin E[subscript 2] (PGE[subscript 2]) production were attenuated in Helicobacter-infected, Trif deficient but not MyD88-/- mice. While infection attenuated IR-induced cytokine production in wildtype and MyD88-/- mice, there was no further decrease in Trif deficient mice. These data indicate distinct roles for MyD88 and Trif in IR-induced inflammation and chronic, undetected infections such as Helicobacter alter the use of the adaptor proteins to induce damage.
Keywords: Mouse; Toll-like receptors; Helicobacter